Toward an East Asian exchange rate regime - Chung, Duck-Koo, 1948-; Eichengreen, Barry J. (Brookings Institution Press, 2007)
"Analyzes the feasibility of continued exchange rate pegging in East Asia and explores alternatives, including some form of regional monetary integration. Argues for coordinating the adjustment of Asian currencies against the dollar and sketches scenarios for the creation of an Asian central bank and a single Asian currency"--Provided by publisher